5-Aminolevulinic Acid-derived Tumor Fluorescence: The Diagnostic Accuracy of Visible Fluorescence Qualities as Corroborated by Spectrometry and Histology and Postoperative Imaging. Issue 3 (12th December 2013) - Stummer, Walter; Tonn, Jörg-Christian; Goetz, Claudia; Ullrich, Winfried; Stepp, Herbert; Bink, Andrea; Pietsch, Thorsten; Pichlmeier, Uwe
Abstract: BACKGROUND: 5-Aminolevulinic acid is used for fluorescence-guided resections. During resection, different macroscopic fluorescence qualities ("strong, " "weak") can be distinguished that help guide resections. OBJECTIVE: This prospective study was designed to assess the reliability of visible fluorescence qualities by spectrometry, pathology, and imaging. METHODS: Thirty-three patients with malignant gliomas received 5-aminolevulinic acid (20 mg/kg). After debulking surgery, standardized biopsies were obtained from tissues with "weak" and "strong" fluorescence and from nonfluorescing near and distant brain for blinded assessment of cell density and tissue type (necrosis, solid or infiltrating tumor, normal tissue). The positive predictive value was calculated. Unresected fluorescing tissue was navigated for blinded correlation to postoperative magnetic resonance imaging (MRI). Receiver operating characteristic curves were generated for assessing the classification efficiency of spectrometry. RESULTS: "Strong" fluorescence corresponded to greater spectrometric fluorescence, solidly proliferating tumor, and high cell densities, whereas "weak" fluorescence corresponded to lower spectrometric fluorescence, infiltrating tumor, and medium cell densities. The positive predictive value was 100% in strongly fluorescing tissue and 95% in weakly fluorescing tissue. Spectrometric fluorescence was detected in marginal tissue without macroscopic fluorescence. Depending on the threshold, spectrometry displayed greater sensitivity but lower specificity (accuracy 88.4%). Residual MRI enhancement in the tumor bed was detected in 15 of 23 (65%) patients with residual fluorescence, but in none of the patients without residual fluorescence. CONCLUSION: Macroscopic fluorescence qualities predict solid and infiltrating tumor, providing useful information during resection. Fluorescence appears superior to contrast enhancement on MRI for indicating residual tumor. Spectrometry, on the other hand, is more sensitive but less specific, depending on threshold definition.